Epidemiological Studies of the Respiratory System in a Cohort of People Exposed to Chronic Radiation Exposure - L. D. Mikryukova (Эпидемиология и вакцинопрофилактика, 2025)
Diseases of the respiratory system are leading in the structure of oncopathology in persons exposed to chronic radiation exposure in the low dose range. The objective of the work is characterize malignant neoplasms of the respiratory system in the Southern Urals Population Exposed to Radiation cohort over a long period of observation (71 years).Materials and methods. The South Urals Population Exposed to Radiation (SUPER) Cohort by accidents at the Mayak Production Association consists of 62 592 persons. We have detected 1023 cases of death from malignant neoplasms of respiratory system during the 71-year follow-up period. The total number of person-years at risk was 1 964 136. The study used a descriptive and analytical epidemiological method.Results. Deaths from malignant neoplasms of the respiratory system in the Southern Urals Population Exposed to Radiation cohort of the accidentally exposed population were registered in 898 men and 125 women. Mortality from respiratory cancer is significantly higher in men compared to women. The dependence of mortality growth on the age of initiation of exposure and its increase was revealed. Mortality is higher in the Russian ethnic group of the population compared with the ethnic group of Tatars and Bashkirs for all periods of observation, except for the period from 2016 to 2020. An increase in mortality from neoplasms of the respiratory system was revealed with an increase in the age reached and the age of initiation of exposure. The risk of mortality from of respiratory cancer is significantly higher in smokers.Conclusions. The study of oncopathology of respiratory tract in exposed people is undoubtedly of scientific and practical interest. The results can serve as a basis for development and improvement of preventive care programs for the affected population.